Lietuviškų klaviatūrų problemos ir jų sprendimo būdai - Maskeliūnas, Saulius (Information & Media, 2008)
Šiame darbe aptariama QWERTY klaviatūros ir jai alternatyvių klaviatūros išdėstymo būdų konkurencija; nagrinėjami klaviatūrų palyginimo ir vertinimo kriterijai; apibendrinami Europoje naudojamų lotyniškos abėcėlės klaviatūrų ypatumai; aptariami Lietuvoje naudojamų klaviatūrų privalumai ir trūkumai, pristatomas ‘skaičiukinės’ klaviatūros visavertiškumo padidinimo būdas; aptariamas lietuviškų raidžių išdėstymas QWERTY klaviatūros mobiliuosiuose telefonuose ir delniniuose kompiuteriuose;pateikiamos išvados.Problems of Lithuanian keyboard layouts and their solutionsSaulius MaskeliūnasSummaryThe paper presents an overview of keyboard layouts: QWERTY and other layouts competing with it, European keyboards for languages based on Latin alphabet; criteria for comparison of alternative keyboard layouts are indicated. Two competing Lithuanian keyboard layouts are contrasted: QWERTY (with Lithuanian diacritical letters on the row of numbers), and ĄŽERTY (Lithuanian standard LST 1582:2000 layout). It is shown how to increase the maturity of the Lithuanian QWERTY keyboard: adding the possibilities to type Lithuanian double and single quotation marks, dash, acute accent (“Liet”), and accented letters (“Lietkirt”); the corresponding DLL and setup packages are built and given for free usage. The question of possible Lithuanian keyboard layouts on various mobile devices is considered, as well.